2016
DOI: 10.1155/2016/6058916
|View full text |Cite
|
Sign up to set email alerts
|

Neck Circumference May Be a Better Alternative to Standard Anthropometric Measures

Abstract: This paper evaluates neck circumference as a metabolic risk marker. Overweight/obese, nondiabetic Hispanics, 40–65 years old, who are free of major cardiovascular diseases, were recruited for the San Juan Overweight Adults Longitudinal Study (SOALS). Baseline exams were completed by 1,206 participants. Partial correlation coefficients (r) and logistic models adjusted for age, gender, smoking status, and physical activity were computed. Neck circumference was significantly correlated with waist circumference (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
119
3
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(144 citation statements)
references
References 40 publications
(42 reference statements)
13
119
3
9
Order By: Relevance
“…NC showed the strongest association with IAS and IAD. This is in concordance with our previous study reporting that NC might be a better predictor of cardio‐metabolic risk . Fat % has not been evaluated in previous studies and we found a significant association with continuous IAS, a significant trend for IAD, but no significant associations were seen between extreme quartiles of fat % and high IABPD.…”
Section: Discussionsupporting
confidence: 92%
“…NC showed the strongest association with IAS and IAD. This is in concordance with our previous study reporting that NC might be a better predictor of cardio‐metabolic risk . Fat % has not been evaluated in previous studies and we found a significant association with continuous IAS, a significant trend for IAD, but no significant associations were seen between extreme quartiles of fat % and high IABPD.…”
Section: Discussionsupporting
confidence: 92%
“…Although these studies carried in different populations (including young adults, elderly people, and population of overweight or obesity), the results were coincident. Our findings were in agreement with these studies (Joshipura et al., ; Li et al., ; Yan et al., ), in which showed NC was associated with overweight or obesity. It was conferred that NC might be a useful tool for identifying Mets and obesity.…”
Section: Discussionsupporting
confidence: 94%
“…Another cross‐sectional survey of population‐based data among 2,092 cases of elderly Chinese (Yan et al., ) showed that NC was strongly associated with BMI and WC, and NC was significantly independent indicators for obesity. Joshipura, Munoz‐Torres, Vergara, Palacios, & Perez () investigated 1,206 participants of overweight or obesity aged from 40 to 65 years and found the highest (compared to the lowest) tertile had a higher association with Mets. Although these studies carried in different populations (including young adults, elderly people, and population of overweight or obesity), the results were coincident.…”
Section: Discussionmentioning
confidence: 99%
“…Due to cultural factors, the measurement of hip or WC may be difficult in certain situations [26]. Measurement of NC may be more useful in morbidly obese people, bedridden patients, and pregnant women [27].…”
Section: Discussionmentioning
confidence: 99%